The Effect of Learners’ first language on their Writings in English - Elwerfalli, Dr : Intesar (مجلة كلية الاداب, 2022)
Writing is a complex task for learners particularly when one writes in a second language (Al Buainain, 2007). A number of studies (e.g. Hussein and Mohammed, 2010) revealed that many L2 learners are influenced by their first language when writing in English. This study aims at exploring L2 learners writing skills difficulties through analysing their errors and identifying whether their first language has a key effect in their writings in English. To achieve the aims of the study, English writing samples of 30 Libyan students from the College of Education in Benghazi were examined. After errors were collected, they were categorized according to the following classifications: mechanic, semantic, grammatical, and word order errors.